Editorial: New Themes in Analytic Dogmatic Theology - Arcadi, James M.; Farris, Joshua R. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2018)
Analytic theology (AT) is a particular approach to theology and the study of religion that engages with the tools, categories, and methodological concerns of analytic philosophy. As a named-entity, AT arrived on the academic scene with the 2009 Oxford University Press publication, Analytic Theology: New Essays in the Philosophy of Theology, edited by Oliver D. Crisp and Michael C. Rea. AT was arguably represented, prior to this publication, by the proto-analytic theologian Richard Swinburne in his noteworthy works on Christian doctrine (e.g. Providence and the Problem of Evil, Responsibility and Atonement, The Christian God, Faith and Reason, and The Resurrection of God Incarnate), as well as by other professional philosophers of religion such as Alvin Plantinga, Nicholas Wolterstorff, Richard Swinburne, William Alston, Eleonore Stump, Robert and Marilyn McCord Adams, Basil Mitchell, Keith Yandell, Paul Helm, and Stephen T. Davis, among others. These philosophers were addressing such topics as the coherence of theism, the rationality of religious belief, and the contributions of such philosophical theologians of the medieval past including Thomas Aquinas or William Ockham and those from modernity including René Descartes and Jonathan Edwards. Yet, the impetus for utilizing analytic philosophy to treat these topics emerged, not from the theological side of the conversation, but from the philosophical side. Anachronistically, then, the term “analytic theology” seems to aptly describe the work of these philosophers of religion.